A blocking material for risk control of polluted groundwater and preparation method thereof

By developing a blocking material containing multiple components, the problem of groundwater pollution in industrial production sites is solved, efficient interception of pollutants and safety guarantee of groundwater resources is achieved, and good environmental stability and cost-effectiveness are achieved.

CN117258749BActive Publication Date: 2025-02-11HEBEI YUHUAN ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311087681.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-11
Estimated Expiration
2043-08-28

AI Technical Summary

Technical Problem

The groundwater pollution problem in industrial production sites is difficult to effectively solve due to the high concentration of pollutants and large spatial spread, which leads to serious threats to groundwater resources.

Method used

开发一种污染地下水风险管控用阻断材料,含膨润土、煤矸石、碱改性百香果壳、改性吸附剂和活性碳纤维,通过其良好的吸附能力和环境稳定性,在恶劣地下水环境中形成阻断区,阻断污染物的扩散。

Benefits of technology

This blocking material can exist for a long time in a harsh environment, keep its performance unchanged, effectively block most pollutants, ensure the safety of groundwater resources, and use industrial waste to achieve comprehensive utilization of resources and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of groundwater pollution control, and specifically discloses a blocking material for risk control of polluted groundwater and a preparation method thereof. The blocking material for risk control of polluted groundwater provided by the present invention comprises a powder and a water material, and the powder comprises the following components: 35% to 55% bentonite, 15% to 30% coal gangue, 5% to 15% alkali-modified passion fruit shell, 20% to 40% modified adsorbent and 0.5% to 1.5% activated carbon fiber; the modified adsorbent is a medical stone adsorbent modified by water glass. The blocking material for risk control of polluted groundwater provided by the present invention has a large specific surface area and a dense pore structure. When used in the risk control of polluted groundwater, it is conducive to multiple reactions such as adsorption-ion exchange-filtration-precipitation with groundwater pollutants, and can block most pollutants; it can exist for a long time in a harsh groundwater environment and keep its performance unchanged, and the blocking effect is sustainable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of groundwater pollution control, and specifically discloses a blocking material for risk control of polluted groundwater and a preparation method thereof. Background Art

[0002] Groundwater is one of the most precious resources for human survival. Industrial production sites are currently the most polluted and complex sites, and there are also many corresponding pollution factors, such as wastewater discharge, solid waste sedimentation, pipeline leakage, transportation and storage of hazardous chemicals, etc. These hazardous media contain a large amount of soil, groundwater, etc. Compared with other types of site pollution, industrial production site pollution has the characteristics of high pollutant concentration and large spatial diffusion, including inorganic heavy metal pollution, organic chemical pollution and their combined pollution, which seriously threatens the groundwater of the site. The discharge of chemical wastewater and the leachate of industrial solid waste sediments are the main causes of groundwater pollution. Due to the large number of various pollutants in this area, if they are not treated in time, they may cause a series of diseases and have a great impact on human health.

[0003] At present, the main technologies for remediating groundwater pollution in industrial sites include in-situ remediation technology, ex-situ remediation treatment technology, and monitored natural attenuation remediation technology. Among them, the ex-situ remediation treatment technology and monitored natural attenuation remediation technology have greater limitations; while the in-situ remediation technology focuses on the flow channel of groundwater and blocks pollutants through certain active prevention and control measures. It has the advantages of high efficiency, convenience, low investment, and little disturbance to the surrounding environment. The in-situ treatment method has a short development time, mainly including source cleaning liquid technology, source gas oscillation technology, and origin reflection zone remediation technology. The source cleaning liquid technology is to immediately enter the organic solvent of the cleaning liquid into the polluted water, melt, transfer, and concentrate the pollutants in a unified area, extract the solution, and purify the groundwater body. It is not suitable for groundwater remediation at ex-situ remediation sites; the source gas oscillation technology is only suitable for volatile pollutants; the origin reflection zone remediation technology must be scientifically planned for groundwater pollution.

[0004] Traditional sewage treatment methods cannot meet the needs of groundwater pollution control in industrial sites, and special materials for groundwater pollution control are still very scarce. Therefore, it is urgent to improve the blocking materials used to prevent groundwater pollution, and form a pollutant blocking area behind the anti-seepage wall by grouting, so as to achieve precise control of the polluted site and efficient interception of pollutants, and ensure the safety of groundwater resources. Summary of the invention

[0005] In response to the above problems, the present invention provides a blocking material for groundwater pollution risk control and a preparation method thereof. The blocking material for groundwater pollution risk control has strong adsorption capacity and good environmental stability, and can exist for a long time in a harsh groundwater environment and maintain unchanged performance.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] A blocking material for controlling the risk of groundwater pollution comprises a powder and a water material. The powder comprises the following components in percentage by mass: 35% to 55% of bentonite, 15% to 30% of coal gangue, 5% to 15% of alkali-modified passion fruit shell, 20% to 40% of a modified adsorbent and 0.5% to 1.5% of activated carbon fiber; the modified adsorbent is a medical stone adsorbent modified by water glass.

[0008] Compared with the prior art, in the blocking material for risk control of groundwater pollution provided by the present invention, bentonite has excellent cation exchange capacity, and has certain buffering, attenuation and blocking capabilities for pollutants, and can be applied to extreme environments such as acidic and alkaline environments with high pollution loads; coal gangue is a solid waste discharged during coal mining and coal washing. It can be used in the blocking material for risk control of groundwater pollution as a good filter filler to filter suspended matter in groundwater and save the amount of natural minerals; passion fruit shell has good adsorption performance for anions, and alkali-modified passion fruit shell can improve the adsorption effect of the blocking material for risk control of groundwater pollution on anions in groundwater pollutants; after water glass modification The medical stone adsorbent has a large specific surface area and a dense pore structure, which greatly increases the reaction active sites between pollutants and materials and the capture capacity of active materials, and can achieve effective adsorption of various organic matter and heavy metal ions in contaminated groundwater; the surface of activated carbon fiber has nanometer-scale pore size, small volume, small filtration resistance, large specific surface area, and is acid-resistant, solvent-resistant, and has high mechanical strength. A trace amount of activated carbon fiber is dispersed in the blocking material for risk control of contaminated groundwater, which plays a great reinforcing role, and can ensure that the blocking material for risk control of contaminated groundwater does not fall off under the action of strong water flow, greatly extending the service life of the blocking material for risk control of contaminated groundwater.

[0009] The blocking material for risk control of polluted groundwater used in the present invention has a large specific surface area and a dense pore structure, which is conducive to multiple reactions such as adsorption-ion exchange-filtration-precipitation with groundwater pollutants, and can block most pollutants; it has good environmental stability, can exist for a long time in a harsh groundwater environment (strong acid or strong alkali, various types of pollutants, dynamic water scouring, etc.) and maintain the same performance, and the blocking effect is sustainable. In addition, coal gangue and passion fruit shells are industrial wastes. The present invention realizes the comprehensive utilization of industrial solid wastes, is more green and environmentally friendly, and the cost is greatly reduced, and has high practical value and promotion value.

[0010] Preferably, the water material includes unpolluted surface water or groundwater.

[0011] Preferably, the mass ratio of the powder to the water is 1:(5-6).

[0012] Controlling the mass ratio of powder to water within the above range can ensure that the blocking material used for groundwater pollution risk control has a moderate consistency, meeting the pumping requirements while having a certain strength.

[0013] Preferably, the bentonite has a particle size of 5 to 12 μm.

[0014] Preferably, the particle size of the coal gangue is 10 to 15 mm.

[0015] Preferably, the preparation method of the alkali-modified passion fruit shell comprises the following steps: crushing the passion fruit shell to obtain passion fruit shell powder; adding the passion fruit shell powder into an alkaline solution, immersing at 80-100° C., washing, and drying to obtain the alkali-modified passion fruit shell.

[0016] Preferably, the particle size of the passion fruit shell powder is 0.15 to 0.25 mm.

[0017] Preferably, the alkaline solution is a 3-6 mol / L sodium hydroxide solution or a potassium hydroxide solution, and the volume mass ratio of the alkaline solution to the passion fruit shell powder is (10-15) mL:1 g; and the immersion time is 2-5 h.

[0018] The invention immerses the passion fruit shell in an alkaline solution to remove the pigment and pectin of the passion fruit shell, thereby preventing the pigment and pectin from affecting the adsorption of anions in the contaminated groundwater.

[0019] Preferably, the method for preparing the modified adsorbent comprises the following steps: impregnating medical stone into water glass, and calcining the impregnated medical stone to obtain the modified adsorbent.

[0020] The medical stone of the invention has high adsorption property. The medical stone is immersed in water glass, which is composed of oligosilicic acid and high-polysilicic acid. The oligosilicic acid contains cage structures such as monosilicic acid, chain disilicate, chain trisilicic acid, cyclotetrasilicic acid, cubic octasilicic acid, etc. After the medical stone is immersed in water glass, a film composed of oligosilicic acid is formed inside the pores and on the surface of the medical stone. The cage-structured oligosilicic acid such as cyclotetrasilicic acid and cubic octasilicic acid changes the pore structure of the medical stone, greatly increases the adsorption capacity of the medical stone for groundwater pollutants, and after calcination, the oligosilicic acid permanently resides in the pores of the medical stone through Si-O-Si or Si-O-Al linking bonds, thereby obtaining a medical stone adsorbent with a larger adsorption capacity.

[0021] Preferably, the particle size of the medical stone is 50 to 90 μm, and the specific surface area is 200 m 2 / g or more, pore volume is 0.6m 3 / g or more, and the static water absorption rate is above 40%.

[0022] Preferably, the modulus of the water glass is 2.5-3, and the concentration is 2.5-3wt%.

[0023] The present invention controls the modulus of water glass within the above range, which is easy to produce a pore structure of oligomers with a cubic structure and has a greater buffering effect on the acidity of oligomeric silicic acid in the water glass.

[0024] Preferably, the solid-to-liquid ratio of the medical stone to water glass is 1 g: (2.5-5) mL.

[0025] Preferably, the immersion temperature is 15-30° C. and the immersion time is 2.5-3 hours.

[0026] The present invention adopts an impregnation method to allow water glass molecules to fully diffuse into the interior and surface of the medical stone, forming a water glass film as a new pore structure of the medical stone, thereby improving the adsorption capacity of the modified adsorbent.

[0027] Preferably, the calcination temperature is 400-550° C. and the calcination time is 2.5-5 hours.

[0028] The calcination of the present invention allows the oligosilicic acid to permanently reside in the pores of the medical stone through Si-O-Si or Si-O-Al links, thereby obtaining a medical stone adsorbent with a larger adsorption capacity.

[0029] Preferably, the average length of the activated carbon fiber is 90-120 μm, and the diameter of the single fiber is 0.5-2 μm.

[0030] For example, the activated carbon fiber is a carbon fiber activated at high temperature, and the carbon fiber can be at least one of phenolic-based fiber, PAN-based fiber, viscose-based fiber or asphalt-based fiber. The present invention does not limit the preparation method of the activated carbon fiber, as long as it can have a nanometer-level pore size, and various commercially available activated carbon fibers can also be used.

[0031] The surface of the activated carbon fiber of the present invention has a nanometer-scale pore size, a small volume, a small filtration resistance, a large specific surface area, and is acid-resistant, solvent-resistant, and has high mechanical strength. The activated carbon fiber is evenly dispersed between the components to form a three-dimensional spatial network structure, which can play a good reinforcement role on the surrounding rock while treating pollutants; a certain amount of activated carbon fiber is configured in the blocking material for risk control of contaminated groundwater, so that the adsorption layer will not cause adsorption resistance due to the deposition of debris generated by adsorption, and will not cause powdering due to changes in the acid-base environment during adsorption regeneration, causing secondary pollution.

[0032] It is worth noting that in the powder of the blocking material for risk control of contaminated groundwater provided by the present invention, each component has a particle size of different levels. The blocking material for risk control of contaminated groundwater formed after the components in specific amounts are evenly mixed has moderate density, permeability and porosity, and can achieve multiple effects such as multi-level adsorption-ion exchange-filtration-precipitation, thereby achieving precise control of contaminated sites and efficient interception of pollutants, preventing the spread of deep-seated pollution sources in industrial sites, and ensuring the safety of groundwater resources in industrial sites.

[0033] The present invention provides a method for preparing a blocking material for controlling the risk of groundwater pollution, comprising the following steps:

[0034] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell into the water material, and mixing them evenly to obtain a first mixed material;

[0035] S2, adding modified adsorbent and activated carbon fiber to the first mixture in batches, mixing evenly, to obtain a second mixture;

[0036] S3, allowing the second mixture to stand and be hydrated for 16 to 20 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0037] The preparation method of the blocking material for groundwater contamination risk control provided in the present application is simple to operate. During the static hydration process of the blocking material for groundwater contamination risk control, the activated carbon fibers can be evenly dispersed therein to form a three-dimensional spatial network structure, which greatly improves the mechanical properties and scour resistance of the blocking material for groundwater contamination risk control and extends its service life.

[0038] The present invention also provides an application of a blocking material for risk control of polluted groundwater in risk control of polluted groundwater.

[0039] The blocking material for risk control of contaminated groundwater of the present invention can be applied to risk control of contaminated groundwater in industrial sites, and the pollutants in the contaminated groundwater may include organic matter, heavy metal ions, dyes, sulfates, nitrates and other substances.

[0040] The blocking material for risk control of contaminated groundwater provided by the present invention is applied to the risk control of contaminated groundwater. Since the blocking material for risk control of contaminated groundwater has a large specific surface area and a dense pore structure, it can undergo multiple reactions such as adsorption-ion exchange-filtration-precipitation with groundwater pollutants, and can block most pollutants, forming a pollutant blocking area behind the anti-seepage wall; at the same time, it has good environmental stability, can exist for a long time in harsh groundwater environments (strong acid or strong alkali, various types of pollutants, dynamic water scouring, etc.) and maintain unchanged performance, and the blocking effect is sustainable. DETAILED DESCRIPTION

[0041] In a first aspect, the present invention provides a blocking material for risk control of polluted groundwater, comprising a powder and a water material, wherein the powder comprises the following components in percentage by mass: 35% to 55% bentonite, 15% to 30% coal gangue, 5% to 15% alkali-modified passion fruit shell, 20% to 40% modified adsorbent and 0.5% to 1.5% activated carbon fiber; the modified adsorbent is a medical stone adsorbent modified by water glass; the water material comprises unpolluted surface water or groundwater; the mass ratio of the powder to the water material is 1:(5 to 6).

[0042] The particle size of the bentonite is 5-12 μm; the particle size of the coal gangue is 10-15 mm; the particle size of the alkali-modified adsorbent is 0.15-0.25 mm; the particle size of the modified adsorbent is 50-120 μm; the average length of the activated carbon fiber is 90-120 μm, and the diameter of the single fiber is 0.5-2 μm.

[0043] In a second aspect, the present invention provides a method for preparing a blocking material for controlling the risk of groundwater contamination, comprising the following steps:

[0044] S0, preparing alkali-modified passion fruit shell and modified adsorbent respectively;

[0045] The preparation method of the alkali-modified passion fruit shell comprises the following steps: crushing the passion fruit shell to obtain passion fruit shell powder; adding the passion fruit shell powder into an alkali solution, immersing at 80-100° C., washing, and drying to obtain the alkali-modified passion fruit shell;

[0046] The particle size of the passion fruit shell powder is 0.15-0.25 mm; the alkaline solution is a 3-6 mol / L sodium hydroxide solution or a potassium hydroxide solution, and the volume mass ratio of the alkaline solution to the passion fruit shell powder is (10-15) mL:1 g; and the immersion time is 2-5 h.

[0047] The preparation method of the modified adsorbent comprises the following steps: impregnating medical stone into water glass, and calcining the impregnated medical stone to obtain the modified adsorbent;

[0048] The particle size of the medical stone is 50 to 90 μm, and the specific surface area is 200 m 2 / g or more, pore volume is 0.6m 3 / g or more, and the static water absorption rate is more than 40%; the modulus of the water glass is 2.5-3, and the concentration is 2.5-3wt%; the solid-liquid ratio of the medical stone to the water glass is 1g:(2.5-5)mL; the temperature of the impregnation is 15-30°C, and the time is 2.5-3h; the temperature of the calcination is 400-550°C, and the time is 2.5-5h.

[0049] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell into the water material, and mixing them evenly to obtain a first mixed material;

[0050] S2, adding modified adsorbent and activated carbon fiber to the first mixture in batches, mixing evenly, to obtain a second mixture;

[0051] S3, allowing the second mixture to stand and be hydrated for 16 to 20 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0052] The mixing is carried out under stirring at a rate of 700 to 900 rpm.

[0053] In a third aspect, the present invention also provides an application of a blocking material for risk control of polluted groundwater in risk control of polluted groundwater.

[0054] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] Example 1

[0056] This embodiment provides a blocking material for risk control of polluted groundwater, including powder and water, wherein the water is unpolluted surface water, and the mass ratio of the powder to the water is 1:5.5. In terms of mass percentage, the powder is composed of the following components: 40% bentonite with a particle size of 10 μm, 20% coal gangue with a particle size of 12 mm, 10% alkali-modified passion fruit shell with a particle size of 0.2 mm, 29% modified adsorbent with a particle size of 80 to 90 μm, and 1% activated carbon fiber with an average length of 100 μm and a monofilament diameter of 0.5 to 2 μm.

[0057] The above-mentioned blocking material for risk control of contaminated groundwater is obtained by the following preparation method:

[0058] S01, preparing the alkali-modified passion fruit shell: crushing the passion fruit shell to obtain passion fruit shell powder with a particle size of 0.2 mm; adding the passion fruit shell powder to a 5 mol / L sodium hydroxide solution, immersing at 90° C. for 4 h, wherein the mass volume ratio of the passion fruit shell powder to the sodium hydroxide solution is 1 g:12 mL, washing, and drying to obtain the alkali-modified passion fruit shell;

[0059] S02, preparing the modified adsorbent: preparing a modified adsorbent having a particle size of 80 μm and a specific surface area of ​​200 m 2 / g or more, pore volume of 0.6m 3 / g or more and a static water absorption rate of more than 40% are impregnated into water glass with a modulus of 2.8 and a concentration of 2.8wt%, wherein the solid-liquid ratio of the medical stone to the water glass is 1g:4mL, and the medical stone is impregnated at 20°C for 3h, and then the impregnated medical stone is calcined at 500°C for 4h to obtain a modified adsorbent with a particle size of 80 to 90μm;

[0060] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell with different particle sizes into the water material, stirring for 25 minutes to mix evenly, with a rotation speed of 800 rpm, to obtain a first mixture;

[0061] S2, adding the modified adsorbent and activated carbon fiber to the first mixture in batches, stirring for 25 minutes to mix evenly, with a rotation speed of 800 rpm, (for example, the modified adsorbent and activated carbon fiber are equally divided into 2 parts, added in 2 times, stirring for 10 minutes after the first batch is added, and continuing to stir for 15 minutes after the second batch is added), to obtain a second mixture;

[0062] S3, allowing the second mixture to stand and be hydrated for 18 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0063] The average micropore size of the blocking material for groundwater contamination risk control was found to be 142 nm, the porosity was 71.35%, and the permeability coefficient was 1.3×10 7cm / s (see Table 1).

[0064] Example 2

[0065] This embodiment provides a blocking material for risk control of polluted groundwater, including powder and water, wherein the water is unpolluted surface water, and the mass ratio of the powder to the water is 1:5. In terms of mass percentage, the powder is composed of the following components: 35% bentonite with a particle size of 5 μm, 18.5% coal gangue with a particle size of 10 mm, 5% alkali-modified passion fruit shell with a particle size of 0.25 mm, 40% modified adsorbent with a particle size of 50 to 100 μm, and 1.5% activated carbon fiber with an average length of 90 μm and a monofilament diameter of 0.5 to 2 μm.

[0066] The above-mentioned blocking material for risk control of contaminated groundwater is obtained by the following preparation method:

[0067] S01, preparing the alkali-modified passion fruit shell: crushing the passion fruit shell to obtain passion fruit shell powder with a particle size of 0.25 mm; adding the passion fruit shell powder to a 6 mol / L sodium hydroxide solution, immersing at 80° C. for 5 h, wherein the amount ratio of the passion fruit shell powder to the sodium hydroxide solution is 1 g:10 mL, washing, and drying to obtain the alkali-modified passion fruit shell;

[0068] S02, preparing the modified adsorbent: preparing a modified adsorbent having a particle size of 50 μm and a specific surface area of ​​200 m 2 / g or more, pore volume of 0.6m 3 / g or more and a static water absorption rate of more than 40% are impregnated into a water glass with a modulus of 2.5 and a concentration of 2.5wt%, wherein the solid-liquid ratio of the medical stone to the water glass is 1g:5mL, and the medical stone is impregnated at 15°C for 3h, and then the impregnated medical stone is calcined at 400°C for 5h to obtain a modified adsorbent with a particle size of 50 to 100μm;

[0069] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell with different particle sizes into the water material, stirring for 20 minutes to mix evenly, with a rotation speed of 900 rpm, to obtain a first mixture;

[0070] S2, adding the modified adsorbent and activated carbon fiber to the first mixture in batches, stirring for 20 minutes to mix evenly, rotating at 900 rpm, (for example, the modified adsorbent and activated carbon fiber are equally divided into 2 parts, added in 2 times, stirring for 10 minutes after the first batch is added, and stirring for 10 minutes after the second batch is added), to obtain a second mixture;

[0071] S3, allowing the second mixture to stand and be hydrated for 16 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0072] After testing, the average micropore size of the blocking material for groundwater contamination risk control was 150nm, the porosity was 72.62%, and the permeability coefficient was 1.4×10 7 cm / s (see Table 1).

[0073] Example 3

[0074] This embodiment provides a blocking material for risk control of polluted groundwater, including powder and water, wherein the water is unpolluted surface water, and the mass ratio of the powder to the water is 1:6. In terms of mass percentage, the powder is composed of the following components: 55% bentonite with a particle size of 9 μm, 15% coal gangue with a particle size of 15 mm, 8.5% alkali-modified passion fruit shell with a particle size of 0.25 mm, 20% modified adsorbent with a particle size of 50 to 100 μm, and 1.5% activated carbon fiber with an average length of 90 μm and a monofilament diameter of 0.5 to 2 μm.

[0075] The above-mentioned blocking material for risk control of contaminated groundwater is obtained by the following preparation method:

[0076] S01, preparing the alkali-modified passion fruit shell: crushing the passion fruit shell to obtain passion fruit shell powder with a particle size of 0.25 mm; adding the passion fruit shell powder to a 3 mol / L sodium hydroxide solution, immersing at 100° C. for 2 h, wherein the ratio of the passion fruit shell powder to the sodium hydroxide solution is 1 g:15 mL, washing, and drying to obtain alkali-modified passion fruit shell;

[0077] S02, preparing the modified adsorbent: preparing a modified adsorbent having a particle size of 50 μm and a specific surface area of ​​200 m 2 / g or more, pore volume of 0.6m 3 / g or more and a static water absorption rate of more than 40% are impregnated into a water glass with a modulus of 2.5 and a concentration of 2.5wt%, wherein the solid-liquid ratio of the medical stone to the water glass is 1g:5mL, and the medical stone is impregnated at 25°C for 3h, and then the impregnated medical stone is calcined at 400°C for 5h to obtain a modified adsorbent with a particle size of 50 to 100μm;

[0078] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell with different particle sizes into the water material, stirring for 30 minutes to mix evenly, with a rotation speed of 700 rpm, to obtain a first mixture;

[0079] S2, adding the modified adsorbent and activated carbon fiber to the first mixture in batches, stirring for 30 minutes to mix evenly, with a rotation speed of 700 rpm, (for example, the modified adsorbent and activated carbon fiber are equally divided into 2 parts, added in 2 times, stirring for 15 minutes after the first batch is added, and stirring for 15 minutes after the second batch is added), to obtain a second mixture;

[0080] S3, allowing the second mixture to stand and be hydrated for 20 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0081] The average micropore size of the blocking material for groundwater contamination risk control was found to be 134 nm, the porosity was 70.54%, and the permeability coefficient was 1.2×10 7 cm / s (see Table 1).

[0082] Example 4

[0083] This embodiment provides a blocking material for risk control of polluted groundwater, including powder and water, wherein the water is unpolluted surface water, and the mass ratio of the powder to the water is 1:5. In terms of mass percentage, the powder is composed of the following components: 35% bentonite with a particle size of 5 μm, 29.5% coal gangue with a particle size of 15 mm, 15% alkali-modified passion fruit shell with a particle size of 0.2 mm, 20% modified adsorbent with a particle size of 90 to 100 μm, and 0.5% activated carbon fiber with an average length of 120 μm and a monofilament diameter of 0.5 to 2 μm.

[0084] The above-mentioned blocking material for risk control of contaminated groundwater is obtained by the following preparation method:

[0085] S01, preparing the alkali-modified passion fruit shell: crushing the passion fruit shell to obtain passion fruit shell powder with a particle size of 0.2 mm; adding the passion fruit shell powder to a 5 mol / L potassium hydroxide solution, immersing at 90° C. for 4 h, wherein the amount ratio of the passion fruit shell powder to the potassium hydroxide solution is 1 g:12 mL, washing, and drying to obtain the alkali-modified passion fruit shell;

[0086] S02, preparing the modified adsorbent: preparing a modified adsorbent having a particle size of 90 μm and a specific surface area of ​​200 m 2 / g or more, pore volume of 0.6m 3 / g or more and a static water absorption rate of more than 40% of medical stone is impregnated into a water glass with a modulus of 3 and a concentration of 3wt%, wherein the solid-liquid ratio of the medical stone to the water glass is 1g:2.5mL, and the medical stone is impregnated at 30°C for 2.5h, and then the impregnated medical stone is calcined at 550°C for 2.5h to obtain a modified adsorbent with a particle size of 90 to 100μm;

[0087] S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell with different particle sizes into the water material, stirring for 25 minutes to mix evenly, with a rotation speed of 800 rpm, to obtain a first mixture;

[0088] S2, adding the modified adsorbent and activated carbon fiber to the first mixture in batches, stirring for 25 minutes to mix evenly, with a rotation speed of 800 rpm, (for example, the modified adsorbent and activated carbon fiber are equally divided into 2 parts, added in 2 times, stirring for 10 minutes after the first batch is added, and continuing to stir for 15 minutes after the second batch is added), to obtain a second mixture;

[0089] S3, allowing the second mixture to stand and be hydrated for 18 hours to obtain a blocking material for controlling the risk of groundwater pollution.

[0090] After testing, the average micropore size of the blocking material for groundwater contamination risk control was 131nm, the porosity was 70.01%, and the permeability coefficient was 1.1×10 7 cm / s (see Table 1).

[0091] Comparative Example 1

[0092] This comparative example provides a blocking material for risk control of groundwater contamination. The specific components are similar to those of Example 1, except that the modified adsorbent is replaced with kaolin of equal mass content.

[0093] The specific preparation steps of the blocking material for risk control of contaminated groundwater are the same as those in Example 1, except that the preparation of the modified adsorbent is omitted and the modified adsorbent is replaced with kaolin of the same mass content.

[0094] The test results show that the average micropore size of the blocking material for groundwater contamination risk control is 30nm, the porosity is 65.21%, and the permeability coefficient is 0.53×10 7 cm / s (see Table 1).

[0095] Comparative Example 2

[0096] This comparative example provides a blocking material for controlling the risk of groundwater pollution. The specific components are similar to those of Example 1, except that it does not contain activated carbon fiber and the content of the modified adsorbent is 30%.

[0097] The specific preparation steps of the above-mentioned blocking material for risk control of contaminated groundwater are the same as those in Example 1, except that no activated carbon fiber is added.

[0098] After testing, the average micropore size of the blocking material for risk control of contaminated groundwater was 82nm, the porosity was 69.24%, and the permeability coefficient was 0.68×10 7 cm / s (see Table 1).

[0099] Performance Testing

[0100] Compressive strength determination: Standard test pieces of Φ50mm×100mm were prepared using the blocking materials for risk control of contaminated groundwater of Examples 1 to 4 and Comparative Examples 1 to 2, and the strength when compressed to deformation was measured using a pressure testing machine. To ensure accuracy, the average value of the three standard test pieces in the same group was taken. The specific compressive strength data are shown in Table 1.

[0101] Table 1 Performance of blocking materials for risk control of groundwater pollution in Examples 1 to 4 and Comparative Examples 1 to 2

[0102]

[0103] It can be seen from the above table that the blocking material for groundwater pollution risk control in the embodiment of the present invention has a good permeability coefficient, and the water permeability of the blocking material for groundwater pollution risk control can greatly reduce the interference of grouting on the groundwater flow field; the modified adsorbent and activated carbon fiber in the present invention can significantly improve the porosity and permeability parameters of the blocking material for groundwater pollution risk control; the activated carbon fiber in the present invention can significantly improve the compressive strength of the blocking material for groundwater pollution risk control.

[0104] Pollutant removal test of contaminated groundwater simulating industrial sites

[0105] The pollutant content of the contaminated groundwater in the simulated industrial site is shown in Table 2, and the dynamic adsorption column test of the blocking material for the risk control of contaminated groundwater is conducted. The adsorption column is a plexiglass column with a length of 100 cm and an inner diameter of 4 cm. The plexiglass column contains 30 cm high river sand as a filling medium. The blocking materials for the risk control of contaminated groundwater in Examples 1 to 4 and Comparative Examples 1 to 2 are used as active media and are evenly filled in the plexiglass column. The filling height is 60 cm. The contaminated groundwater in the simulated industrial site is added to the adsorption column at a speed of 5 mL / min by a peristaltic pump, and the concentration of each ion in the outlet is monitored every 30 minutes. The test results show that after 4 hours, the adsorption capacity of the blocking material for the risk control of contaminated groundwater for five ions reaches equilibrium. The specific test data are shown in Table 3.

[0106] Table 2 Pollutant content of contaminated groundwater in simulated industrial sites

[0107]

[0108] Table 3 Pollutant removal rate of blocking materials for risk control of polluted groundwater in Examples 1 to 4 and Comparative Examples 1 to 2 (%)

[0109] Pollutants Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 <![CDATA[Pb 2+ ]]> 96.7 95.9 95.8 95.1 88.1 89.4 <![CDATA[Cu 2+ ]]> 95.8 95.7 95.1 94.8 87.5 89.0 <![CDATA[Fe 2+ ]]> 93.1 93.2 92.4 92.1 86.0 87.2 <![CDATA[Mn 2+ ]]> 90.4 90.7 91.0 89.6 81.3 85.1 <![CDATA[Zn 2+ ]]> 89.2 90.1 89.4 88.9 74.2 78.4

[0110] It can be seen from the above table that the blocking material for risk control of contaminated groundwater provided by the present invention can effectively remove pollutants in contaminated groundwater in simulated industrial sites.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A blocking material for risk control of groundwater pollution, characterized in that: The invention comprises powder and water, wherein the powder comprises the following components by weight percentage: 35% to 55% bentonite, 15% to 30% coal gangue, 5% to 15% alkali-modified passion fruit shell, 20% to 40% modified adsorbent and 0.5% to 1.5% activated carbon fiber; the modified adsorbent is medical stone adsorbent modified by water glass; The preparation method of the modified adsorbent comprises the following steps: The medical stone is immersed in water glass, and the immersed medical stone is calcined to obtain a modified adsorbent.

2. The blocking material for controlling the risk of contaminated groundwater according to claim 1, characterized in that: The water material includes uncontaminated surface water or groundwater; and / or The mass ratio of the powder to the water is 1:(5-6).

3. The blocking material for controlling the risk of contaminated groundwater according to claim 1, characterized in that: The particle size of the bentonite is 5 to 12 μm; and / or The particle size of the coal gangue is 10-15 mm; and / or The average length of the activated carbon fiber is 90-120 μm, and the diameter of the single fiber is 0.5-2 μm.

4. The blocking material for controlling the risk of contaminated groundwater according to claim 1, characterized in that: The preparation method of the alkali-modified passion fruit shell comprises the following steps: Grinding passion fruit shell to obtain passion fruit shell powder; The passion fruit shell powder is added into an alkaline solution, immersed at 80-100° C., washed and dried to obtain an alkali-modified passion fruit shell.

5. The blocking material for controlling the risk of groundwater contamination according to claim 4, characterized in that: The particle size of the passion fruit shell powder is 0.15-0.25 mm; and / or The alkaline solution is a 3-6 mol / L sodium hydroxide solution or a potassium hydroxide solution, and the volume mass ratio of the alkaline solution to the passion fruit shell powder is (10-15) mL:1 g; and / or The immersion time is 2 to 5 hours.

6. The blocking material for controlling the risk of contaminated groundwater according to claim 1, characterized in that: The particle size of the medical stone is 50-90 μm, and the specific surface area is 200 m 2 / g or more, pore volume is 0.6m 3 / g or more, static water absorption rate is more than 40%; and / or The modulus of the water glass is 2.5-3, and the concentration is 2.5wt%-3wt%; and / or The solid-to-liquid ratio of the medical stone to water glass is 1g:(2.5-5)mL.

7. The blocking material for controlling the risk of contaminated groundwater according to claim 1, characterized in that: The immersion temperature is 15-30°C and the immersion time is 2.5-3h; and / or The calcination temperature is 400-550° C. and the calcination time is 2.5-5 hours.

8. The method for preparing the blocking material for controlling the risk of groundwater contamination according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, weighing each component according to the designed ratio, adding bentonite, coal gangue and alkali-modified passion fruit shell into the water material, mixing evenly, to obtain a first mixed material; S2, adding modified adsorbent and activated carbon fiber to the first mixture in batches, mixing evenly, to obtain a second mixture; S3, allowing the second mixture to stand and be hydrated for 16 to 20 hours to obtain a blocking material for controlling the risk of groundwater pollution.

9. Use of the blocking material for risk control of contaminated groundwater according to any one of claims 1 to 7 in risk control of contaminated groundwater.

Citation Information

Patent Citations

  • Coal ash and bentonite composite groundwater pollution interception wall and preparation method thereof

    CN108383437A

  • Quick and efficient underground water pollution stopping material and application method thereof

    CN110656656A